Локализованные волновые структуры в неравновесных средах - Даниленко, В.А.; Скуратовский, С.И. (Проблемы управления и информатики, 2012)
Досліджуються хвильові розв’язки математичної моделі нерівноважного середовища, яка є одновимірною системою рівнянь гідродинамічного типу з нелокальним динамічним рівнянням стану. Показано, що тривимірний фазовий простір динамічної системи, яка описує хвильові розв’язки моделі, містить граничні цикли різної кратності, гетероклінічні та гомоклінічні петлі, а також хаотичні атрактори. Wave solutions to a mathematical model for nonequilibrium medium are investigated. This model is written in the form of a one-dimensional system of hydrodynamic equations with a nonlocal dynamical equation of state. Using qualitative analysis methods, it is shown that the three-dimensional phase space of the dynamical system describing wave solutions of the model contains limit cycles of different multiplicity, heteroclinic and homoclinic loops, as well as chaotic attractors.